(untitled) (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
This study aims to investigate the phenomenon of law enforcement apparently disregarding justice in viral social media cases in Indonesia exploring its causes manifestations and implications for the country s legal system and society The research employed a qualitative methodology combining in depth interviews with key stakeholders focus group discussions social media content analysis and a comprehensive literature review The findings reveal a complex interplay of factors contributing to this phenomenon including a significant disconnect between public expectations and law enforcement realities the influence of political connections on case handling and the emergence of digital vigilantism The study also identified gaps in existing legal frameworks a lack of digital literacy among both the public and law enforcement officials and the psychological toll on officers facing public pressure These results highlight the need for multifaceted reforms in law enforcement practices legal structures and public communication strategies to address the challenges posed by viral social media cases and maintain public trust in the justice system < p>